Chat Widgets for Science Libraries. - John J. Meier (Issues in Science and Technology Librarianship)
This paper describes chat widgets, chunks of code that can be embedded on a web site to appear as an instant messaging system, and how they can be used on a science library web site to better serve library users. Interviews were conducted concerning experiences at science and humanities libraries and more similarities than differences were discovered. High user satisfaction and subject-specific questions were noted by librarians using widgets on their subject research guide web pages. Increased use of these services resulted from embedding widgets on existing web pages rather than linking to separate chat pages [ABSTRACT FROM AUTHOR]